Analisis Pengelolaan Keuangan Syariah Usaha Mikro Kecil Menengah Di Candi Muaro Jambi - Dodi Kurniawan; Titin Agustin Nengsih; Lidya Angraeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this thesis is to manage Islamic finance MSMEs at Muaro Jambi Temple, to find out the obstacles in managing MSME sharia finance at Muaro Jambi Temple and to find out the efforts of MSMEs in financial management at Muaro Jambi Temple. This thesis uses a qualitative approach with data collection methods through observation, interviews, and documentation. Based on the research conducted, the following results and conclusions are obtained: MSME Islamic Financial Management in Muaro Jambi Temple is carried out by trying only to take what is lawful and good, lawful way of acquisition: through trade that applies voluntarily and willingly, lawful method of acquisition: act fairly and avoid doubts and lawful. How to use: Help each other and avoid excessive risks. Obstacles in MSME Islamic Financial Management at Muaro Jambi Temple include personal needs and business turnover that are not separated and limited knowledge. Efforts in MSME Islamic Financial Management at Muaro Jambi Temple include the use of the budget in the needs that will be carried out so that the business being run can benefit, recording is done to anticipate losses occurring or expenditures occurring, so that income will also be clearer when recording, reporting is done made not just written numbers but have information. Exercising control by fully implementing control over the financial management of its business.